SEA BUCKTHORN (HIPPOPHAE SP.): HIGHLY POTENTIAL UNDERUTILISED PLANT IN SIKKIM: A REVIEW - THANGJAM ANAND SINGH,; PRAKASH KUMAR SARANGI,; NGANKHAM JOYKUMAR SINGH, (The Bioscan, 2015)
Seabuckthorn (SB) has gained tremendous importance as a multi utility plant. SB products include foodstuffs, healthcare products, cosmetics, medicine and many more. Countries like China, Russia, and Canada exploited the plant with immense commercial success. Seabuckthorn grow in Lachung and Lachen area of North Sikkim. The berries were mainly use as dye and meat tenderiser and leaves as fodder in Sikkim. SB holds the potential of changing the socio economic status of rural Sikkim if the plant is exploited like China and elsewhere but government must have proper policy and R&D backup to realised the potential.